First‐Principles Study of Twin Boundaries and Stacking Faults in β‐Ga2O3 - Mengen Wang; Sai Mu; James S. Speck; Chris G. Van de Walle (Advanced Materials Interfaces)
Abstract This study uses density functional theory calculations to explore the energetics and electronic structures of planar defects in monoclinic β‐Ga2O3, including twin boundaries (TBs) and stacking faults (SFs). TBs on the (001)A, (001)B, (100)A, (100)B, and (−102) planes are examined; it is found that (100)A has a very low formation energy (0.01 Jm‐2), consistent with its observation in a number of experiments. For SFs, SFs on the (100) plane have much lower energy (0.03 Jm‐2) than SFs formed on the (010) and (001) planes. Growth on a (100) surface is thus expected to result in more planar‐defect formation, again consistent with experimental observations. In spite of their higher energies, TBs and SFs on planes other than (100) have been experimentally observed in epitaxial layers. Their origins are explained in terms of coalescence of different growth regions when the growth direction changes, or when low‐energy TBs on the growing surface lead to domains with different twinning orientation.